Influence of Pilate therapy in post natal women with back pain - B. Kanase, Suraj; kumar patil, Sanjay (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Regaining functional independence after delivery is a challenging task for any female. It is mainly due to the impairment that follows in the postpartum period. Postnatal back pain is the predisposing factor for most of the problems that arise. Prevalence is increasing day by day. Purpose : The purpose of this study was to find out a gold standard for managing back pain, which is a global problem in postnatal women. Pilates therapy has been tried out for it. Methods : A pilot study where 20 postnatal females having problems of back pain and abdominal weakness were included. They were assessed on the basis of a visual analogue scale and manual muscle testing. Pilates therapy was given for a period of 6 weeks. Results : Using a paired t-test, the scoring was calculated for changes within the group. Pilate therapy was found to have an extremely significant difference in the reduction of back pain and improving muscle strength statistically. Conclusion: Pilates therapy is very effective in reducing back pain in postnatal women. It significantly improves muscle strength and flexibility of abdominal muscles.